Transições ontológicas: perspectivas transdisciplinares no estudo do despertar espiritual - Rezinovsky, Daniel (2022)
This research aimed to investigate the phenomenological and ontological dimensions of the experience of spiritual awakening. A review of the classical literature of comparative mysticism was carried out, as well as a review of contemporary research in areas such as philosophy of mind, psychology, neuroscience and religious studies. We sought to identify central phenomenological elements of the experience of spiritual awakening, such as non-duality, unity, consciousness without objects and the state of pure consciousness, in order to utilize them as starting points for a theoretical discussion of the ontology of mysticism and more specifically, of spiritual awakening itself. In this regard, philosophical perspectives such as idealism and panpsychism were explored, in order to obtain hermeneutic and ontological frameworks that interpret awakening differently from the materialist position. The interpretation that awakening consists in a strictly subjective and personal event was contrasted with an ontological view in which it naturally emerges from a self-aware cosmos. This dissertation constitutes a preliminary contribution within the scientific study of spiritual awakening, in order to foster future investigations of a theoretical and empirical character